Towards earlier diagnosis of 22q11 deletions. Issue 6 (1st December 1999) - Tobias, E S; Morrison, N; Whiteford, M L; Tolmie, J L
Abstract : Over a 7 year period, 551 patients were investigated for the presence of a chromosome 22q11 deletion by fluorescence in situ hybridisation. Analysis of the presenting features of the 67 individuals with this chromosome deletion permitted us to devise guidelines to facilitate early diagnosis.